The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.20546/ijcmas.2019.811.027
|View full text |Cite
|
Sign up to set email alerts
|

Trait Associations and Path Coefficient Analysis for Seed Yield and Morphological Characters in Greengram (Vigna radiata (L.) Wilczek.)

Abstract: Genetic variability, heritability along with genetic advance of traits, their association and direct and indirect effects on yield are essential for crop improvement. One hundred and three greengram genotypes were studied to assess variability and degree to which various plant traits associate with seed yield. Sufficient genetic variability was observed for plant height, pods per plant and seed yield. Number of primary branches per plant, number of clusters per plant and pod length showed lesser variability wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…For example, parent Sampeong (G3) exhibited positive and significant GCA effect and had high mean value for seed yield per plant, number of branches per plant, number of clusters per plant, and number of pods per plant. ese findings agreed with the reports of Zubair et al [16] and Latha et al [17].…”
Section: General Combining Abilitysupporting
confidence: 93%
See 1 more Smart Citation
“…For example, parent Sampeong (G3) exhibited positive and significant GCA effect and had high mean value for seed yield per plant, number of branches per plant, number of clusters per plant, and number of pods per plant. ese findings agreed with the reports of Zubair et al [16] and Latha et al [17].…”
Section: General Combining Abilitysupporting
confidence: 93%
“…e significant mean squares of GCA and SCA indicated the importance of the effects of additive and dominant genes, while pod length was only significant for SCA, indicating the importance of the influence of nonadditive genes. e significant effects of general combining ability and specific combining ability on mungbean for plant height, number of pods, days to maturity, seed yield, and weight of 100 seeds were also reported by [5,6,16,17].…”
Section: Analysis Of Variancementioning
confidence: 96%
“…and Viraj et al (2020). On contrary,Latha et al (2018) reported comparatively higher additive variance for branches per plant andNath et al (2018) for days to 50% flowering, primary branches, clusters per plant and seed yield/plant in greengram.…”
mentioning
confidence: 88%
“…When a cross for any trait has a negative sign for "h," it means that the parents with the alleles that cause the characteristics' low values contributed to the dominating effects. Therefore, when desirable segregants become available, selection for these features should likewise be postponed until a later generation (Latha et al 2018).…”
Section: Mukherjee1 Et Almentioning
confidence: 99%